Association of serum lipid profile with coronary computed tomographic angiography-derived morphologic and functional quantitative plaque markers - Baumann, Stefan; Becher, Tobias; Rutsch, Marlon; Behnes, Michael; Stach-Jablonski, Ksenija; Henzler, Thomas; Schönberg, Stefan; Weiß, Christel; Borggrefe, Martin; Akın, Ibrahim; Loßnitzer, Dirk; Kryeziu, Philipp; et al. (Journal of thoracic imaging, 2019)
Purpose:Recent advances in image quality of coronary computed tomographic angiography (cCTA) have enabled improved characterization of coronary plaques. Thus, we investigated the association between quantitative morphological plaque markers obtained by cCTA and serum lipid levels in patients with su
Gesehen am 28.10.2019